PELATIHAN STUDI KELAYAKAN BISNIS USAHA FOTOCOPY HAFIS PROGRAM MBKM MAHASISWA UIGM - Ani, Anis Anggreq; Hertati, Lesi; Asharie, Asmawati (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2022)
The photocopying business is a small business whose implementation does not require a high level of education, so it can help open up employment opportunities for human resources with low education and will reduce the unemployment rate. will later boost people's purchasing power and in time can contribute to the regional economy. Therefore, this implementation aims to determine the feasibility of the "Hafis" photocopying business. In this implementation, all of them are photocopy service businesses around the school. The HAFIS photocopy business feasibility study training is an initiative to improve the entrepreneurial skills of students in the Master's Program in Business Management and Entrepreneurship (MBKM). The aim of this training is to equip students with knowledge and skills in analyzing business feasibility, especially in micro, small and medium enterprises (MSMEs) in the photocopying sector. This training consists of a series of sessions covering the basic concepts of business feasibility studies, risk analysis methodology, marketing strategies, financial analysis, as well as legal and regulatory aspects related to photocopy businesses. Apart from that, the training also provides insight into the development of MSMEs in the photocopy sector, market potential and opportunities that can be exploited. The training method involves a combination of theory sessions, case studies, group discussions, and business feasibility analysis simulations. The training participants are MBKM Program students who have the interest and potential to be involved in the world of entrepreneurship, especially in the photocopy sector